Endoscopic retrograde cholangiopancreatography in patients with periampullary diverticula: Technical details, classification, and timing of surgical treatment (Annals of Medical Research, 2021)
Aim: Periampullary duodenal diverticula may create difficulties for selective common bile duct cannulation during endoscopic retrograde cholangiopancreatography (ERCP).Material and Methods: For the study, the technical details and findings of ERCP and demographic features of 724 patients without duodenal diverticula and 92 patients with duodenal diverticula who underwent ERCP.Results: The mean age was 73.09 ± 15.32 years for the 92 patients with PAD (group A) and 60,2 ± 18.85 years for the 724 patients without duodenal diverticulum (group B). Forty-eight percent of the study sample was aged over 65 years, 54.3% were female and 45.7% were male. Duodenal diverticulum was present in 11.3% of the patients. In addition, 22 (23.9%) patients in the PAD group and 155 (21.4%) patients without duodenal diverticula required a second ERCP (P = 0.583). The mean duration of hospitalization was 6.67 ± 6.23 days in patients with duodenal diverticula and 6.17 ± 5.16 days in the control group and the mean cost of hospitalization was $ 442.02 ± 512.06.Conclusion: In conclusion, ERCP may not always be difficult in patients with a diverticulum in the periampullary region, and the difficulty of the procedure depends on the location of the papillary orifice and the type of the diverticulum. In patients with periampullary diverticula, it would be appropriate to consider surgical treatment in the presence of failed CBD cannulation and large stones that cannot be removed from the CBD.
Keywords: Common bile duct; diverticulum; endoscopic retrograde cholangiopancreatography